The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.bjc.6604114
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of age and carcinoembryonic antigen in the prognosis of colorectal cancer

Abstract: The aim of this study was to verify through relative survival (an estimate of cancer-specific survival) the true prognostic factors of colorectal cancer. The study involved 506 patients who underwent locally radical resection. All the clinical, histological and laboratory parameters were prognostically analysed for both overall and relative survival. This latter was calculated from the expected survival of the general population with identical age, sex and calendar years of observation. Univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Our multivariate analysis showed that old age (≥60 years), being node positive and a M1 status were the independent factors affecting overall survival, and this was regardless of the cancer site, the same as was reported elsewhere (24,25). Colonic obstruction in large bowel cancer is generally considered a poor prognostic factor.…”
Section: Discussionsupporting
confidence: 83%
“…Our multivariate analysis showed that old age (≥60 years), being node positive and a M1 status were the independent factors affecting overall survival, and this was regardless of the cancer site, the same as was reported elsewhere (24,25). Colonic obstruction in large bowel cancer is generally considered a poor prognostic factor.…”
Section: Discussionsupporting
confidence: 83%
“…It is noteworthy that patients with tumour cells in their follow‐up BM investigation were more frequently of the female gender and of more advanced age when compared with those without tumour cells. Assuming that MRD positivity might be a negative predictive factor for cancer‐related morbidity, these observations do not concur with the results of most studies evaluating gender or age‐related prognosis and might have been caused by the small number of investigated patients [30,31].…”
Section: Discussionmentioning
confidence: 63%
“…However, a statistical tendency towards elevated CEA levels (≥ 5) was registered in patients who had identifiable tumour cells at both times or at least at the second BM puncture. As an elevated CEA level indicates a higher risk of relapse [31,33] this observation might be of interest. The follow‐up period in this study was too short to permit conclusions about the influence of the 1‐year postsurgery MRD results on clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…13 The age-, gender-, and calendar year-specific death rates available from national Italian mortality tables (ISTAT, Istituto Nazionale di Statistica) were used to calculate the expected deathsand, thus, the expected survival. Age changes according to individual birthdays in every year of the follow-up were 14 The observed deaths recorded in the population of patients at the end of the follow-up period and the difference between the observed deaths and the cumulative expected probability of death during the corresponding period (i.e., excess mortality, which has to be taken into account for relative survival) are the variables that can be used in both survival calculations and multivariate analyses. When evaluating the curves of relative survival, we have to remember that if observed and expected deaths are equal (i.e., there is not excess mortality) their ratio is 1, and the curve shows a plateaux of 100%.…”
Section: Statisticsmentioning
confidence: 99%